Sparking Signals - Baier, G. (Springer, 2017)
Protein phosphorylation is an essential post-translational modification that modulates cell–cell communication. Substrate phosphorylation by protein kinases controls intracellular signal transduction pathways that mediate cell proliferation, migration, differentiation, and metabolism. The importance of the protein kinase family is underscored by numerous disease states that arise due to dysregulation of kinase activity. Recent progress in understanding the molecular regulation of kinases has led to the development of new therapeutics based on the inhibition of kinase activity. Inhibitors that target protein kinases have proven efficacious in clinical settings and their continued development is the current focus of many drug discovery groups.